2009
DOI: 10.3354/meps07905
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and persistence of species-rich patches in a species-poor landscape: role of a structure-forming subtidal barnacle

Abstract: Some sessile invertebrates are capable of maintaining space in barren habitats produced by sea urchins, thereby creating species-rich patches in a species-poor landscape. We sought to determine the role of a large and common barnacle, Austrobalanus imperator, in the establishment and persistence of these species-rich patches. Barnacle density was modified in 2 experiments at sites in southeastern Australia. The first experiment concerned community establishment and involved the addition of barnacles in 4 densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Through removal experiments, Sutherland (1978) showed that the presence of the bryozoan Schizoporella unicornis and the ascidian Styela plicata led to the formation of previously observed 'multiple stable points' during succession (Sutherland 1974). Similarly, Blum et al (2007) showed that the presence of the invasive ascidian Ciona intestinalis dominated space and depressed species richness, while Davis & Ward (2009) showed that the presence of the barnacle Austrobalanus imperator is essential in the formation of a species rich community by promoting the recruitment of other sessile invertebrates. Still other studies have used addition and removal experiments to demonstrate lowered diversity by the blue mussel Mytilus edulis (Durr & Wahl 2004), recruitment facilitation among the ascidians Pyura spinifera and Cnemidocarpa pedata (Davis 1996), and reduced settlement due to the presence of 4 different species of resident ascidians (Osman & Whitlatch 1995).…”
Section: Introductionmentioning
confidence: 95%
“…Through removal experiments, Sutherland (1978) showed that the presence of the bryozoan Schizoporella unicornis and the ascidian Styela plicata led to the formation of previously observed 'multiple stable points' during succession (Sutherland 1974). Similarly, Blum et al (2007) showed that the presence of the invasive ascidian Ciona intestinalis dominated space and depressed species richness, while Davis & Ward (2009) showed that the presence of the barnacle Austrobalanus imperator is essential in the formation of a species rich community by promoting the recruitment of other sessile invertebrates. Still other studies have used addition and removal experiments to demonstrate lowered diversity by the blue mussel Mytilus edulis (Durr & Wahl 2004), recruitment facilitation among the ascidians Pyura spinifera and Cnemidocarpa pedata (Davis 1996), and reduced settlement due to the presence of 4 different species of resident ascidians (Osman & Whitlatch 1995).…”
Section: Introductionmentioning
confidence: 95%